2010
DOI: 10.1111/j.1751-2980.2010.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient differentiation of newly derived human embryonic stem cells from discarded blastocysts into hepatocyte‐like cells

Abstract: Three hES cell lines have been successfully isolated and cultured from discarded human blastocysts. The hES cells can be efficiently differentiated into hepatocyte-like cells using the EB system. These cells possess the potential for treatment of liver diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…A typical stem cell cluster‐like structure (Lu et al . )emerged (Fig. , DMSO, white *), of which the cells in the center were very small (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A typical stem cell cluster‐like structure (Lu et al . )emerged (Fig. , DMSO, white *), of which the cells in the center were very small (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Even though feeder‐free cultures using matrigel have been developed, enabling ES cell culture in BAL devices, the risk of introducing murine viruses from matrigel is of concern. There are many reports on the in vitro differentiation of embryonic stem cells to hepatocyte‐like cells . However, none of the available protocols have been delivered at scale and have thereby limit the application of ES‐derived hepatocytes in a BAL .…”
Section: Cell Sources For Liver Tissue Engineeringmentioning
confidence: 99%
“…Following the HD culture, hEBs may undergo suspension culture for further compaction before being used in a differentiation protocol. A few studies have shown differentiation of HD-produced human EBs to several cell types, including hematopoietic cells [52], cardiomyocytes [53], and hepatocytes [54]. These investigations indicate propensities of the HD-produced EBs to progress toward cell types of all three germ layers.…”
Section: Figmentioning
confidence: 99%